A function for EGF receptor signaling in expanding the developing brain in Drosophila. - Page, D.T. (Current Biology, 2003)
In invertebrates and vertebrates, neural midline cells secrete signals that pattern the central nervous system (CNS). However, an important part of the developing insect brain, involved in functions such as olfaction and feeding behavior, is positioned lateral to the foregut and lacks neural cells at the midline. Could the foregut substitute for neural midline cells and secrete signals that pattern this part of the brain?In Drosophila embryos, the neural midline marker Single-minded is expressed in foregut cells adjacent to the brain, as are members of the Egf receptor signaling pathway. Removing the function of these molecules results in aberrant proliferation and reduced size in the brain lateral to the foregut.Cells of the brain lateral to the foregut receive an Egf signal from the midline and proliferate in response. A likely source of this signal is the foregut. These findings raise the possibility that the brain lateral to the foregut is an evolutionarily recent addition to the arthropod brain, and that the anterior boundary of the brain neural midline is a conserved feature in bilaterally symmetric animals.